The influences of iron characteristics, operating conditions and solution chemistry on contaminants removal by zero-valent iron: A review. (1st September 2016) - Sun, Yuankui; Li, Jinxiang; Huang, Tinglin; Guan, Xiaohong
Abstract: For successful application of a zero-valent iron (ZVI) system, of particular interest is the performance of ZVI under various conditions. The current review comprehensively summarizes the potential effects of the major influencing factors, such as iron intrinsic characteristics (e.g., surface area, iron impurities and oxide films), operating conditions (e.g., pH, dissolved oxygen, iron dosage, iron pretreatment, mixing conditions and temperature) and solution chemistry (e.g., anions, cations and natural organic matter) on the performance of ZVI reported in literature. It was demonstrated that all of the factors could exert significant effects on the ZVI performance toward contaminants removal, negatively or positively. Depending on the removal mechanisms of the respective contaminants and other environmental conditions, an individual variable may exhibit different effects. On the other hand, many of these influences have not been well understood or cannot be individually isolated in experimental or natural systems. Thus, more research is required in order to elucidate the exact roles and mechanisms of each factor in affecting the performance of ZVI. Furthermore, based on these understandings, future research may attempt to establish some feasible strategies to minimize the deteriorating effects and utilize the positive effects so as to improve the performance of ZVI. Graphical abstract: Highlights: The effects of major influencing factors on the performance of ZVI are reviewed. The mechanisms of various factors affecting the performance of ZVI are summarized. Ratios of kinetic constants with and without the influencing factors are summed. The critical knowledge gaps and future research needs are proposed.